Performance of Mahyco Green Long and Bhaktapur Local Cucumber Cultivars at Different Sowing Dates in Mid-Hill of Nepal - Sharma, MD; GC, YD; Tripathi, KM; Bhattarai, SP (Journal of the Institute of Agriculture and Animal Science, 2005)
An experiment was conducted in split plot design with three replications to determine the optimum date of sowing for commercial cultivation of cucumber at Lamjung Campus, Sundarbazar (750 m asl), Lamjung during December 1999 to November 2000. The cvs. Green Long and Bhaktapur Local were used in the main plot and the sowing dates in the sub-plot. Sowings were done on the 15th of the months December 1999 and February, April, June and August 2000 at an interval of two months. Manure and fertilizers were applied @ 20 t farm yard manure and 120:60:50 NPK kg/ha in all the sowings. Yield attributing characters such as plant stand, vine growth, first male and first female flowers bearing nodes, number of female flowers per plot, sex ratio and number of harvests were insignificantly different in December and February sowings. However, the periods of phenophases such as sowing to the first male and first female flowers and sowing to first harvest and last harvest were significantly longer at December sowing followed by those at February sowing. The three latter sowings showed poor performance in respect to those characters. February sowing produced significantly the highest number of marketable fruits (79.16 thousand/ha) and marketable yield (53.97 t/ha) than the earlier December and three latter sowings. The December sowing also produced significantly higher marketable yield (23.76 t/ha) than June and August sowings. Hence, the cvs. Green Long and Bhaktapur Local could not produce economic yields at April, June and August sowings at Sundarbazar (middle hill) Lamjung. Key words: Cucumber cultivar, sowing date, marketable yield J. Inst. Agric. Anim. Sci. 26:163-166 (2005)